Standard Methods and Criteria Considerations for Residential Noise Complaints - Meszaros, Steve; Toome, Mikhel (Canadian Acoustics, 2017)
Acoustic consultants receive many inquiries about noisy neighbours, particularly from occupants of multi-unit residential buildings. There are currently no standards or regulations that objectively define thresholds for what is considered an annoyance or unacceptable noise intrusion. The lack of standardization for measurements, metrics, and criteria leaves complainants with little to no recourse, even when taking legal action. The development of a standard procedure and criteria would be a significant undertaking, but would be invaluable to acoustic engineers, local municipalities, noise by-law enforcement officers, and the public at large. This paper reviews relevant literature, outlines the major components for consideration in the development of a standard procedure and criteria, and will put forth a recommended framework for a standard approach.